O Psicólogo e o seu fazer na educação: contando uma outra história - Rita de Cassia Vieira (2008)
This research investigates the work of the psychologist in the field of Education, aiming at evaluating this work vis-à-vis the current critique to which it has been submitted. Since the 1980s, psychologists approach in education is considered reductionist, limited, directed to individual and not to collective interests and distant from social, political, economic and ideological issues that pervade educational institutions and the educational process. From this standpoint, psychologists intervention in educational processes, relying on psychometrics and on a clinical approach, is considered as a contribution for social exclusion and school failure of lower class children. My hypothesis is that, although in cases already documented in the literature psychology may have contributed for educational and social exclusion, the work of the psychologist is far from being undifferentiated. It is possible that they work may, in some cases, follow the opposite direction and contribute for the educational and social inclusion of disadvantaged students, when inspired by theoretical perspectives emphasizing the social and cultural genesis of psychological phenomena. The research was developed in Clínica de Psicologia Edouard Claparède of Fundação Helena Antipoff, located in Ibirité, Minas Gerais, Brazil. This clinic is recognized as one of the first institutions to offer psychological services in the State of Minas Gerais, and still exists. Moreover, the Claparède Clinic was founded by Helena Antipoff, a Russian psychologist who pioneered in the establishment and consolidation of applied psychology in the State of Minas Gerais and in Brazil, and who adopted a socio-cultural perspective in Psychology. Therefore, this case-study could provide evidence of a different approach, one that takes into consideration social issues and inclusion. The data were collected through analysis of psychological records adopting a phenomenological perspective , archival documents and semi-structured interviews. The hypothesis was confirmed, since in this institution there is evidence of a differentiated work being developed, in which the socio-cultural interpretation and the educational inclusion of clients are emphasized. Drawing on this analysis, some considerations are made on the importance of a sound theoretical and technical training for psychologists professional work, stemming from the association between teaching, research and extension.